Culturally responsive classrooms: African American male student perceptions - Long, Sheila Faye; Wilburn, Victor Romando (American Journal of Creative Education, 2025)
This paper focuses on the process of conducting and evaluating a medium-sized Midwestern school district of African American male third graders’ academic achievement and their teachers using culturally relevant pedagogy. The evaluation was developed from a pre-test and post-test data analysis to a mixed-method sequential explanatory evaluation. Culturally relevant pedagogy is operationally defined as a student-centered approach to teaching in which the students’ unique cultural strengths are identified and nurtured to promote student achievement and a sense of well-being about their place in the cultural world. This study examined the unique contexts of literacy programs utilized by teachers in African American males’ classrooms and other students of diverse backgrounds. The results demonstrated that African American males exhibited greater self-identification when employing culturally relevant pedagogy in a conducive and supportive learning environment. This series not only enabled teachers to diversify students’ exposure to cultural literature but also increased the students’ literacy scores for elementary readers by focusing on the reading and writing success of diverse students. This program targets key areas of reading comprehension, vocabulary, grammar, and writing in kindergarten through second-grade students. In addition, this study also contributes to our understanding of the challenges that young African American males face in the academic classroom.